Optimization of Na3Zr2Si2PO12 ceramic electrolyte and interface for high performance solid-state sodium battery. Issue 2 (1st February 2019) - Ruan, Yanli; Guo, Fang; Liu, Jingjing; Song, Shidong; Jiang, Ningyi; Cheng, Bowen
Abstract: Poor ionic conductivity of solid-state electrolyte (SE) and high interface resistances between the SE and electrodes are two major challenges for solid-state sodium batteries (SSBs). In this work, an integrate strategy is proposed for improving the ionic conductivity of SE and reducing the interfacial resistance between SE and cathode. The pure-phase Na3 Zr2 Si2 PO12 (NZSP) is prepared by optimizing the composition ratios of the starting materials and is applied as SE for SSBs. The as-prepared NZSP SE achieves a relatively high ionic conductivity of 1.935 × 10 −4 S cm −1 at 25 °C and a good electrochemical stability up to 5 V vs. Na + /Na. The solid-state Na|NZSP|Na symmetrical cell can perform a consistent cycling for 70 h, indicating the excellent chemical and electrochemical stability for SE and SE/Na interface. A composite cathode is fabricated using NZSP and Na3 V2 (PO4 )3 (NVP) particles. The sodiated Nafion is particularly applied as the interface modifier for the cathode to facilitate the ionic contact. At 25 °C, the SSB with NZSP SE and the composite cathode modified by sodiated Nafion delivers a discharge capacity of 81.6 mA h g −1 at the current density of 20 mA g −1 and retains a high capacity of 62.23 mA h g −1 after 50 cycles. These results indicate that optimization of the NZSP electrolyte and the NZSP/NVP interface is an efficient method to achieve the high-performance SSB.